Drivers of Inpatient Hospital Experience Using the HCAHPS Survey in a Canadian Setting. (8th December 2014) - Kemp, Kyle A.; Chan, Nancy; McCormack, Brandi; Douglas‐England, Kathleen
<x xml:space="preserve">Abstract</x> Objective To identify factors associated with patients' overall rating of inpatient hospital care. Data Sources Two years of patient interview data (April 1, 2011 to March 31, 2013), linked to inpatient administrative records. Study Design Patients rated their overall health on a scale of 0 (worst care) to 10 (best care) using the HCAHPS instrument administered via telephone, up to 42 days postdischarge. Logistic regression was used to generate odds ratios for each independent predictor. Data Extraction HCAHPS data were linked to inpatient records based on health care numbers and dates of service. The outcome (overall health experience) was collapsed into two groups (10 vs. 0–9). Principal Findings Overall hospital experience of 0–9 was associated with younger age, male gender, higher level of education, being born in Canada, urgent admission, not having a family practitioner as the most responsible provider service, and not being discharged home. A length of stay of less than 3 days was protective. The c‐statistic for the multivariate model was 0.635. Conclusions Our results are novel in the Canadian population. Several questions for future research have been generated, in addition to opportunities for quality improvement within our own organization.